(untitled) (Medicine Today, 2021)
Introduction: : Preterm birth as a consequence of preterm labour is the major clinical problem associated with perinatal mortality, serious neonatal morbidity and moderate to severe childhood disability and two-thirds of all perinatal deaths. Moreover, preterm labour comprises a large number of low birth weight babies. Global incidence of preterm labour is 5-10% of all births. The aim of this study was to determine the clinical profile and to find out pregnancy outcomes of preterm labour. Materials & Methods: This cross-sectional study was conducted in Sir Salimullah Medical College Mitford Hospital, Dhaka from January 2005 to December 2005. A total 103 gravid women who got admitted with established premature labour pain were included as study patients. Preterm labour associated with severe pre-eclampsia, eclampsia, antepartum haemorrhage and intrauterine fetal death were excluded. Data were collected in a pre-designed questionnaire and analyzed by SPSS software. Results: Incidence of preterm labour was found 6.3%. Among maternal morbidities, puerperal sepsis found to be highest (14.56%) followed by UTI (7.77%), PPH (6.80%), wound infection (5.83%) and retained placenta (3.88%). This study found perinatal mortality 32.0% and morbidity 49.5% of which RDS contributed highest (24.27%) followed by neonatal jaundice (11.65%), septicemia (8.73%), neonatal convulsion (2.91%) and umbilical sepsis (1.94%). Conclusion: Preterm labor followed by preterm birth significantly contributes to maternal morbidity and perinatal morbidity and mortality. Medicine Today 2021 Vol.33(2): 143-146